Preparation of spongy K-Al2O3 composite material and application of spongy K-Al2O3 composite material in lithium battery diaphragm coating
Through the modification and application of spongy K-Al2O3 composite materials, the problems of low ionic conductivity, low wetting and low heat resistance of lithium battery separators are solved, and the overall performance and safety of lithium batteries are significantly improved.
Patent Information
- Application Number
- CN202411906048.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-05-02
AI Technical Summary
The lithium battery separator has problems such as poor wetting and heat resistance and low ionic conductivity.
Using sponge-like K-Al2O3 composite material, by mixing and modifying sponge-like K-Al2O3 porous alumina with polyacrylamide solution, a composite material with good thermal stability and high specific surface area was prepared, and applied to the lithium battery separator coating.
It significantly improves the ionic conductivity, liquid absorption and heat resistance of the lithium battery separator, enhances the working performance and safety of the battery, and reduces the leakage risk of electrolyte.
Smart Images

Figure CN119912699A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of materials for lithium battery diaphragms, and in particular to the preparation of a sponge-like K-Al2O3 composite material and its application in lithium battery diaphragm coatings. Background Art
[0002] In the construction of lithium batteries, the separator is an indispensable component. It is not only responsible for maintaining the physical isolation between the positive and negative electrodes to avoid short circuits, but also must have good ion conductivity so that lithium ions can shuttle freely, thereby achieving effective charging and discharging of the battery. Improving the ionic conductivity of the separator is crucial to improving the overall performance of lithium batteries, which is also a hot area of current materials science research.
[0003] With the growing demand for higher energy density and fast charging in modern electronic devices, it is particularly urgent to develop new diaphragm materials to enhance their ion transmission efficiency and liquid retention capacity. This requires researchers to conduct innovative exploration in material design, microstructure control, and surface modification in order to develop diaphragm products with better comprehensive performance.
[0004] In summary, in-depth research and improvement of the ionic conductivity and liquid absorption and retention rate of lithium battery separators is not only of great significance for improving battery performance, but also of extremely important value for meeting the high standards of future energy storage systems. Summary of the invention
[0005] The present invention proposes a preparation method of a sponge-like K-Al2O3 composite material and its application in a lithium battery separator coating, which solves the problems of poor wettability and heat resistance and low ion conductivity of lithium battery separators in the related art.
[0006] The technical solution of the present invention is as follows: The present invention provides a sponge-like K-Al2O3 composite material, which is obtained by modifying the sponge-like K-Al2O3 porous alumina with polyacrylamide; The sponge-like K-Al2O3 composite material has a particle size D50 of 0.649-0.851 μm, a particle size D90 of 1.552-2.643 μm, a specific surface area of 55-70 m2 / g, a pore size of 10-20 nm, and a porosity of 30%-45%.
[0007] As a further technical solution, the modification method comprises the following steps: The sponge-like K-Al2O3 porous alumina and the polyacrylamide solution are mixed and dried to obtain a sponge-like K-Al2O3 composite material.
[0008] As a further technical solution, the mass concentration of the polyacrylamide solution is 5% to 30%; The mass ratio of the sponge-like K-Al2O3 porous alumina to the polyacrylamide solution is 1-3:7-9.
[0009] As a further technical solution, grinding is further performed after the drying.
[0010] As a further technical solution, the sponge-like K-Al2O3 porous alumina has a particle size D50 of 0.625~0.830μm, a particle size D90 of 1.512~2.536μm, a specific surface area of 55~70m² / g, a pore size of 10~20nm, and a porosity of 30%~45%.
[0011] As a further technical solution, the mixing method includes ultrasonic mixing; During the ultrasonic mixing, the vacuum environment is 0.06-0.08 kPa, the rotation speed is 1000-3000 r / min, the revolution speed is 40-60 r / min, and the ultrasonic frequency is 5-8 kHz.
[0012] The present invention also provides a slurry for lithium battery diaphragm coating, comprising the sponge-like K-Al2O3 composite material, water, an adhesive and a dispersant.
[0013] As a further technical solution, the invention comprises the following components in parts by weight: 40~80 parts of water, 5~10 parts of adhesive, 0.5~1 part of dispersant, 20~40 parts of sponge-like K-Al2O3 composite material.
[0014] As a further technical solution, the adhesive includes an acrylate copolymer solution; The dispersant includes ammonium polyacrylate.
[0015] The present invention also provides a method for preparing a slurry for a lithium battery separator coating, comprising the following steps: S1, mixing the dispersant, water and sponge-like K-Al2O3 composite material for the first time to obtain a mixture; S2. Add the remaining components of the slurry to the mixture for a second mixing to obtain slurry.
[0016] As a further technical solution, the first mixing time is 30-60 min, the rotation speed is 2000-4000 r / min, and the revolution speed is 40-60 r / min; The second mixing time is 30-60 min, the rotation speed is 2000-3000 r / min, the revolution speed is 30-60 r / min, the vacuum environment is 0.06-0.08 kPa, and the ultrasonic frequency is 5-8 kHz.
[0017] The present invention also provides a lithium-ion battery separator, comprising a base film and a coating arranged on at least one side of the base film, wherein the raw material of the coating comprises the sponge-like K-Al2O3 composite material or the slurry or the slurry prepared by the preparation method.
[0018] The present invention also provides a method for preparing a lithium battery separator, comprising the following steps: The slurry or the slurry obtained by the preparation method is coated on one side of the base film and dried to obtain a lithium battery separator.
[0019] As a further technical solution, the coating speed is 10-30 m / min, and the coating thickness after coating is 3-4 μm; The drying temperature is 30-50° C. and the drying time is 1-3 minutes.
[0020] In the present invention, the porous alumina is a sponge-like K-Al2O3 porous alumina. The sponge-like K-Al2O3 composite material modified by polyacrylamide has good thermal stability and can maintain structural stability in a high temperature environment. Adding it to the lithium battery diaphragm coating can reduce the diaphragm shrinkage or expansion problem caused by temperature changes, thereby improving the working performance and safety of the battery under different temperature conditions.
[0021] In the present invention, the sponge-like K-Al2O3 composite material is introduced into the lithium battery separator coating to significantly improve the ionic conductivity of the lithium battery separator, and its porous structure provides more lithium ion transmission channels, reduces the internal impedance of the battery, and thus accelerates the migration rate of lithium ions between the positive and negative electrodes; the porous structure of the sponge-like K-Al2O3 composite material increases the separator's ability to adsorb and retain the electrolyte, helps to form a stable electrolyte interface, improves the battery's cycle life and charge and discharge efficiency, and reduces the risk of electrolyte leakage.
[0022] In the present invention, the sponge-like K-Al2O3 composite material is introduced into the lithium battery separator coating, which can effectively inhibit the growth of lithium dendrites and prevent short circuit and thermal runaway. Its high mechanical strength and tortuous porous structure can block the penetration of lithium dendrites, improve the safety performance of the battery, and avoid the risk of overheating and combustion.
[0023] The working principle and beneficial effects of the present invention are: In the present invention, the sponge-like K-Al2O3 porous alumina has a high porosity. The sponge-like K-Al2O3 porous alumina is subjected to liquid-phase surface modification by using a polyacrylamide solution, so that amino polar groups are grafted on its surface and in its pores. The present invention is applied to lithium-ion battery separators, which helps to improve the liquid absorption and wettability of the separators, ensure the effective transmission of lithium ions, and further improve the overall performance of lithium batteries. In addition, a large number of amino polar groups grafted on the surface of the modified sponge-like K-Al2O3 porous alumina can form coordination bonds with Li ions, thereby constructing Li ion channels inside the separator, helping to improve the transmission efficiency of Li ions, and reducing migration resistance, thereby enhancing the ionic conductivity of the lithium battery separator. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.
[0025] Figure 1 This is the XRD pattern of the sponge-like K-Al2O3 porous alumina of Example 1 of the present invention; Figure 2 This is the SEM image of the sponge-like K-Al2O3 porous alumina of Example 1 of the present invention. DETAILED DESCRIPTION
[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] In the following examples and comparative examples, the particle size D50 of the sponge-like K-Al2O3 porous alumina is 0.625-0.830 μm, the particle size D90 is 1.512-2.536 μm, the specific surface area is 55-70 m² / g, the pore size is 10-20 nm, and the porosity is 30%-45%; The particle size D50 of the sponge-like K-Al2O3 composite material is 0.649~0.851μm, the particle size D90 is 1.552~2.643μm, the specific surface area is 55~70m² / g, the pore size is 10~20nm, and the porosity is 30%~45%; The mass concentration of the acrylate copolymer solution was 20 wt %, which was copolymerized by acrylic acid and acrylamide and purchased from Baoding Lucky Imaging Material Technology Co., Ltd.; The weight average molecular weight of ammonium polyacrylate was 30 million and it was purchased from Shanghai Sanrui Polymer Materials Technology Co., Ltd.; The weight average molecular weight of polyacrylamide is 1 million; PE membrane, porosity is 36%.
[0028] Example 1 Preparation of sponge-like K-Al2O3 composite materials: The sponge-like K-Al2O3 porous alumina and a polyacrylamide aqueous solution with a mass concentration of 10% were placed in a double planetary mixer XFZH-30L for ultrasonic oscillation mixing for 30 minutes, and then placed in an oven for drying and grinding to obtain a sponge-like K-Al2O3 composite material; The mass ratio of sponge-like K-Al2O3 porous alumina and polyacrylamide aqueous solution was 1:9, and the mixture was ultrasonically shaken in a vacuum environment of 0.06 kPa, with a rotation speed of 1000 r / min, a revolution speed of 40 r / min, and an ultrasonic frequency of 5 kHz. The slurry for lithium battery separator coating comprises the following components in parts by weight: 20 parts of sponge-like K-Al2O3 composite material, 74.5 parts of pure water, 5 parts of acrylate copolymer solution, and 0.5 parts of ammonium polyacrylate; Preparation of slurry for lithium battery separator coating: S1, ammonium polyacrylate, pure water and sponge-like K-Al2O3 composite material were mixed for the first time in a double planetary mixer XFZH-30L for 30 minutes to obtain a mixture; S2, adding the remaining components of the slurry to the mixture and mixing for a second time for 30 minutes to obtain a slurry; The first mixing was carried out at an autogenous speed of 2000 r / min and an orbital speed of 40 r / min; the second mixing was carried out under a vacuum environment of 0.06 kPa, at an autogenous speed of 2000 r / min, an orbital speed of 30 r / min, and an ultrasonic frequency of 5 kHz; Preparation of lithium battery separator: A 7 μm PE film was placed on a coating machine filled with slurry for single-side coating, the coating speed was controlled at 10 m / min, and the film was pulled into a drying device by a traction roller and dried at 30° C. for 3 min to obtain a lithium battery separator. The coating thickness on the surface of the lithium battery separator was 2 μm. XRD test results of sponge-like K-Al2O3 porous alumina Figure 1 As shown; SEM test was performed on sponge-like K-Al2O3 porous alumina. Figure 2 shown.
[0029] Example 2 Preparation of sponge-like K-Al2O3 composite materials: The sponge-like K-Al2O3 porous alumina and a polyacrylamide aqueous solution with a mass concentration of 20% were placed in a double planetary mixer XFZH-30L for ultrasonic oscillation mixing for 45 minutes, and then placed in an oven for drying and grinding to obtain a sponge-like K-Al2O3 composite material; The mass ratio of sponge-like K-Al2O3 porous alumina and polyacrylamide aqueous solution was 1:4, and the mixture was ultrasonically shaken in a vacuum environment of 0.07 kPa, with a rotation speed of 2000 r / min, a revolution speed of 50 r / min, and an ultrasonic frequency of 6 kHz; The slurry for lithium battery separator coating comprises the following components in parts by weight: 30 parts of sponge-like K-Al2O3 composite material, 61.3 parts of pure water, 8 parts of acrylate copolymer solution, and 0.7 parts of ammonium polyacrylate; Preparation of slurry for lithium battery separator coating: S1, ammonium polyacrylate, pure water and sponge-like K-Al2O3 composite material were mixed for the first time in a double planetary mixer XFZH-30L for 45 minutes to obtain a mixture; S2, adding the remaining components of the slurry to the mixture and mixing for a second time for 45 minutes to obtain a slurry; The first mixing was carried out at an autogenous speed of 3000 r / min and an orbital speed of 50 r / min; the second mixing was carried out under a vacuum environment of 0.07 kPa, at an autogenous speed of 2500 r / min, an orbital speed of 45 r / min, and an ultrasonic frequency of 6 kHz; Preparation of lithium battery separator: A 7μm PE film was placed on a coating machine filled with slurry for single-sided coating. The coating speed was controlled at 20m / min. The film was pulled into a drying device via a traction roller and dried at 40°C for 2 minutes to obtain a lithium battery separator. The coating thickness on the surface of the lithium battery separator was 2μm.
[0030] Example 3 Preparation of sponge-like K-Al2O3 composite materials: The sponge-like K-Al2O3 porous alumina and a polyacrylamide aqueous solution with a mass concentration of 30% were placed in a double planetary mixer XFZH-30L for ultrasonic oscillation mixing for 60 minutes, and then placed in an oven for drying and grinding to obtain a sponge-like K-Al2O3 composite material; The mass ratio of sponge-like K-Al2O3 porous alumina and polyacrylamide aqueous solution was 3:7, and the mixture was ultrasonically shaken in a vacuum environment of 0.08 kPa, with a rotation speed of 2000 r / min, a revolution speed of 50 r / min, and an ultrasonic frequency of 8 kHz. The slurry for lithium battery separator coating comprises the following components in parts by weight: 40 parts of sponge-like K-Al2O3 composite material, 49 parts of pure water, 10 parts of acrylate copolymer solution, and 1 part of ammonium polyacrylate; Preparation of slurry for lithium battery separator coating: S1, ammonium polyacrylate, pure water and sponge-like K-Al2O3 composite material were mixed for the first time in a double planetary mixer XFZH-30L for 60 minutes to obtain a mixture; S2, adding the remaining components of the slurry to the mixture and mixing for a second time for 60 minutes to obtain a slurry; The first mixing was carried out at a rotation speed of 4000 r / min and an orbital speed of 60 r / min; the second mixing was carried out under a vacuum environment of 0.08 kPa, with a rotation speed of 3000 r / min, an orbital speed of 60 r / min, and an ultrasonic frequency of 8 kHz. Preparation of lithium battery separator: A 7μm PE film was placed on a coating machine filled with slurry for single-sided coating. The coating speed was controlled at 30m / min. The film was pulled into a drying device via a traction roller and dried at 50°C for 1 minute to obtain a lithium battery separator. The coating thickness on the surface of the lithium battery separator was 2μm.
[0031] Example 4 The only difference between this embodiment and embodiment 1 is that pure water is replaced by the oily solvent DMAC.
[0032] Example 5 The difference between this embodiment and embodiment 1 is only the preparation of the lithium battery separator: A 7μm PE film was placed on a coating machine filled with slurry for double-sided coating. The coating speed was controlled at 10m / min. The film was pulled into a drying device via a traction roller and dried at 30°C for 3 minutes to obtain a lithium battery separator. The coating thickness on the surface of the lithium battery separator was 4μm.
[0033] Comparative Example 1 The slurry for lithium battery separator coating comprises the following components in parts by weight: 20 parts of sponge-like K-Al2O3 porous alumina, 74.5 parts of pure water, 5 parts of acrylate copolymer solution, and 0.5 parts of ammonium polyacrylate; Preparation of slurry for lithium battery separator coating: S1, ammonium polyacrylate, pure water, and sponge-like K-Al2O3 porous alumina are mixed for the first time for 30 minutes in a double planetary mixer XFZH-30L to obtain a mixture; S2, adding the remaining components of the slurry to the mixture and mixing for a second time for 30 minutes to obtain a slurry; The first mixing was carried out at an autogenous speed of 2000 r / min and an orbital speed of 40 r / min; the second mixing was carried out under a vacuum environment of 0.06 kPa, at an autogenous speed of 2000 r / min, an orbital speed of 30 r / min, and an ultrasonic frequency of 5 kHz; Preparation of lithium battery separator: A 7μm PE film was placed on a coating machine filled with slurry for single-sided coating. The coating speed was controlled at 10m / min. The film was pulled into a drying device via a traction roller and dried at 30°C for 3 minutes to obtain a lithium battery separator. The coating thickness on the surface of the lithium battery separator was 2μm.
[0034] Comparative Example 2 The slurry for lithium battery separator coating comprises the following components in parts by weight: 20 parts of aluminum oxide (particle size D50: 0.702 μm, particle size D90: 1.998 μm), 74.5 parts of pure water, 5 parts of acrylate copolymer solution, and 0.5 parts of ammonium polyacrylate; Preparation of slurry for lithium battery separator coating: S1. Mix ammonium polyacrylate, pure water and aluminum oxide in a double planetary mixer XFZH-30L for 30 minutes to obtain a mixture; S2, adding the remaining components of the slurry to the mixture and mixing for a second time for 30 minutes to obtain a slurry; The first mixing was carried out at an autogenous speed of 2000 r / min and an orbital speed of 40 r / min; the second mixing was carried out under a vacuum environment of 0.06 kPa, at an autogenous speed of 2000 r / min, an orbital speed of 30 r / min, and an ultrasonic frequency of 5 kHz; Preparation of lithium battery separator: A 7μm PE film was placed on a coating machine filled with slurry for single-sided coating. The coating speed was controlled at 10m / min. The film was pulled into a drying device via a traction roller and dried at 30°C for 3 minutes to obtain a lithium battery separator. The coating thickness on the surface of the lithium battery separator was 2μm.
[0035] Comparative Example 3 The difference between this comparative example and Example 1 is that the polyacrylamide aqueous solution with a mass concentration of 10% is replaced by a PVDF solution with a mass concentration of 10%; the solvent in the PVDF solution is dimethylacetamide, and the model of PVDF is FR903.
[0036] Comparative Example 4 The difference between this comparative example and Example 1 is that the polyacrylamide aqueous solution with a mass concentration of 10% is replaced by an aminosilane coupling agent solution with a mass concentration of 10%; the solvent in the aminosilane coupling agent solution is propanol, and the model of the aminosilane coupling agent is KH-550.
[0037] The following performance tests were performed on the lithium battery separators prepared in Examples 1 to 4 and Comparative Examples 1 to 4 respectively: Air permeability test: Under a pressure of 1.22 kPa, the time required for 100 mL of air to pass through a 1 square inch diaphragm is tested; Shrinkage test: After covering the upper and lower parts of the lithium battery separator with a piece of A4 paper, the separator was placed in an oven at 130°C for 1 hour, and then the transverse (TD) shrinkage and longitudinal (MD) shrinkage of the lithium battery separator were measured; Liquid absorption and liquid retention rate test: Cut 3 diaphragm samples with an area of 50mm×50mm. For diaphragms with a width of less than 50mm, cut 3 full-width diaphragm samples with a length of 50mm, with the side length accurate to 1mm; Weigh the cut sample and record it as m1. Soak the weighed diaphragm in the electrolyte for 30 minutes. Spread a layer of clean industrial wipe paper (area greater than 150mm×150mm) on a flat desktop, take out the sample, quickly place it on the industrial wipe paper, and use another piece of industrial wipe paper to gently press and wipe the free electrolyte on the surface of the diaphragm until the granular electrolyte is no longer visible to the naked eye. Weigh the mass of the dried sample m2, then set it aside for one hour and weigh it, record it as m3.
[0038] The liquid absorption rate and liquid retention rate of the diaphragm are calculated according to the following formulas: Liquid absorption rate = [(m2-m1) / m1] × 100%; Liquid retention rate = [(m3-m1) / m1] × 100%; Where: m1 is the weight of the diaphragm after cutting, in grams (g); m2 is the weight of the diaphragm after immersion, in grams (g); m3 is the weight of the diaphragm after being soaked and left for 1 hour, in grams (g); Take the average value of 3 parallel sample tests and retain the calculation result to one decimal place.
[0039] Ionic conductivity: Draw a curve with the number of diaphragm layers as the horizontal axis and the diaphragm resistance as the vertical axis, and find the slope and linear fit of the curve. When the linear fit is greater than 0.995, the ionic conductivity of the diaphragm is calculated according to the following formula. When the linear fit is less than 0.995, retesting is required.
[0040] R = k × 1; Where: R is the resistance value of one layer of diaphragm, in ohms (Ω); K is the slope of the curve when the fitting degree is greater than 0.995; R S =R×S; Where: R is the resistance value of one layer of diaphragm, in ohms (Ω); Rs is the surface resistance of the diaphragm, in Ω cm 2 ); σ = d / R × S; Where: σ--ionic conductivity of the membrane, in Siemens per centimeter (S / cm); d is the thickness of one layer of diaphragm, in micrometers (μm); R is the resistance value of one layer of diaphragm, in ohms (Ω); S is the area of the diaphragm cut during the test, in square centimeters (cm 2 ).
[0041] The results are shown in Table 1 below.
[0042] Table 1 Performance test results
[0043] Compared with Comparative Examples 1 to 4, the lithium battery separators prepared in Examples 1 to 4 have lower high-temperature shrinkage, higher liquid absorption and liquid retention rates, and higher ionic conductivity, indicating that the use of sponge-like K-Al2O3 porous alumina and the modification of the sponge-like K-Al2O3 porous alumina with a polyacrylamide aqueous solution and its application in lithium-ion battery separator coatings significantly improves the liquid absorption and retention, wettability, ionic conductivity and heat resistance of the lithium-ion battery separator.
[0044] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A sponge-like K-Al2O3 composite material, characterized in that: It is obtained by modifying sponge-like K-Al2O3 porous alumina with polyacrylamide; The sponge-like K-Al2O3 composite material has a particle size D50 of 0.649-0.851 μm, a particle size D90 of 1.552-2.643 μm, a specific surface area of 55-70 m2 / g, a pore size of 10-20 nm, and a porosity of 30%-45%.
2. A sponge-like K-Al2O3 composite material according to claim 1, characterized in that: The modified method comprises the following steps: The sponge-like K-Al2O3 porous alumina and the polyacrylamide solution are mixed and dried to obtain a sponge-like K-Al2O3 composite material.
3. A sponge-like K-Al2O3 composite material according to claim 2, characterized in that: The mass concentration of the polyacrylamide solution is 5% to 30%; The mass ratio of the sponge-like K-Al2O3 porous alumina to the polyacrylamide solution is 1-3:7-9.
4. A sponge-like K-Al2O3 composite material according to claim 2, characterized in that: The drying is followed by a grinding process.
5. A sponge-like K-Al2O3 composite material according to claim 4, characterized in that: The sponge-like K-Al2O3 porous alumina has a particle size D50 of 0.625-0.830 μm, a particle size D90 of 1.512-2.536 μm, a specific surface area of 55-70 m2 / g, a pore size of 10-20 nm, and a porosity of 30%-45%.
6. The sponge-like K-Al2O3 composite material according to claim 2, characterized in that: The mixing method includes ultrasonic mixing; During the ultrasonic mixing, the vacuum environment is 0.06-0.08 kPa, the rotation speed is 1000-3000 r / min, the revolution speed is 40-60 r / min, and the ultrasonic frequency is 5-8 kHz.
7. A slurry for lithium battery separator coating, characterized in that: The sponge-like K-Al2O3 composite material comprises the sponge-like K-Al2O3 composite material according to any one of claims 1 to 6, and further comprises water, an adhesive and a dispersant.
8. The slurry for lithium battery separator coating according to claim 7, characterized in that: The composition comprises the following components in parts by weight: 40~80 parts of water, 5~10 parts of adhesive, 0.5~1 part of dispersant, 20~40 parts of sponge-like K-Al2O3 composite material.
9. The method for preparing a slurry for lithium battery separator coating according to any one of claims 7 to 8, characterized in that: The following steps are involved: S1, mixing the dispersant, water and sponge-like K-Al2O3 composite material for the first time to obtain a mixture; S2. Add the remaining components of the slurry to the mixture for a second mixing to obtain slurry.
10. A lithium ion battery separator, characterized in that: It comprises a base film and a coating arranged on at least one side of the base film, wherein the raw material of the coating comprises the sponge-like K-Al2O3 composite material described in any one of claims 1 to 6, or the slurry described in any one of claims 7 to 8, or the slurry prepared by the preparation method described in claim 9.
Citation Information
Cited By
Spongy high-infiltration lithium ion battery diaphragm coating slurry as well as preparation method and application thereof
CN121812889A